Understanding Binge-Watching: The Role of Dark Triad Traits, Sociodemographic Factors, and Series Preferences - Ângela Leite; Anabela Rodrigues; Sílvia Lopes; Ana Catarina Pereira (Psychiatry International, 2025)
Binge-watching has become a dominant mode of media consumption, yet its psychological underpinnings remain insufficiently explored. This study investigates the influence of dark triad personality traits, sociodemographic factors, and TV series preferences on binge-watching behavior. A Portuguese version of the Binge-Watching Engagement and Symptoms Questionnaire (BWESQ) was validated using a confirmatory factor analysis (CFA), demonstrating strong psychometric properties. Measurement invariance was confirmed across genders through a multigroup CFA, testing configural, metric, scalar, and error variance levels. Model reliability, convergent validity, and discriminant validity were assessed using Cronbach’s alpha, composite reliability, and the average variance extracted (AVE). Multiple linear regression analyses identified significant predictors of binge-watching, including gender, age, professional status, TV series preferences, Machiavellianism, and psychopathy. These findings underscore the role of personality traits and demographic factors in shaping binge-watching behavior, offering insights that may inform psychological interventions to prevent excessive or problematic viewing patterns.